TILAB MAHMUDOV’S CONTRIBUTION TO THE DEVELOPMENT OF NATIONAL AESTHETIC HERITAGE (Scientific journal of the Fergana State University, 2026)
This article analyzes the scientific and theoretical contribution of Tilab Mahmudov to the development of Uzbek national aesthetic thought. His views on art, beauty, morality, and spirituality are examined as a natural continuation of the philosophical tradition of Uzbekistan. The paper highlights Mahmudov’s efforts to preserve national aesthetic heritage and integrate it with modern culture. Furthermore, it emphasizes the significance of his works in shaping the aesthetic consciousness of youth.